2020
DOI: 10.3389/fimmu.2020.521409
|View full text |Cite
|
Sign up to set email alerts
|

A Specific IL6 Polymorphic Genotype Modulates the Risk of Trypanosoma cruzi Parasitemia While IL18, IL17A, and IL1B Variant Profiles and HIV Infection Protect Against Cardiomyopathy in Chagas Disease

Abstract: Background: Chagas disease caused by Trypanosoma cruzi (T. cruzi) affects approximately six million individuals worldwide. Clinical manifestations are expected to occur due to the parasite persistence and host immune response. Herein we investigated potential associations between IL1B, IL6, IL17A, or IL18 polymorphism profiles and cardiomyopathy or T. cruzi parasitemia, as well as the impact of HIV infection on cardiopathy. Methods: Two hundred twenty-six patients and 90 control individuals were analyzed. IL1B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…1B ). Other studies suggested that disruption of IL-6 expression and downstream targets during parasite infection play important roles in T. cruzi pathogenesis ( 5 6 7 47 ). These results suggest that these piRNAs may be important modulators of IL6 and SOCS3 gene expression during the early/acute phase of T. cruzi infection and pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B ). Other studies suggested that disruption of IL-6 expression and downstream targets during parasite infection play important roles in T. cruzi pathogenesis ( 5 6 7 47 ). These results suggest that these piRNAs may be important modulators of IL6 and SOCS3 gene expression during the early/acute phase of T. cruzi infection and pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a need to understand the molecular mechanisms of T. cruzi pathogenesis to facilitate identification of biomarkers and new therapeutic targets. The IL-6 signaling pathway has been suggested to play important roles in experimental and clinical T. cruzi pathogenesis ( 5 6 7 ). IL-6 is a cytokine with diverse roles in endothelial cell function, inflammation, and fibrogenesis ( 8 9 10 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic Chagas disease, cardiac and gastrointestinal manifestations: Whether PWH are more susceptible to cardiomyopathy when co-infected with T. cruzi remains unclear [ 26 ]. One Brazilian group investigated potential associations between T. cruzi parasitemia and the impact of HIV infection on cardiomyopathy [ 36 ]. Their data suggest that HIV infection may protect against the development and progression of cardiopathy, potentially due to a synergistic effect of HIV and/or ART or reduced cellular immunity attenuating a type-1 helper T-cell-mediated response in the myocardium.…”
Section: Presentationsmentioning
confidence: 99%
“…It is more common in PWH with low CD4 cell counts [ 44 ] (particularly less than 100 cells/mm 3 ) and is considered to be an opportunistic infection in people with AIDS. IL-18 serum concentrations may influence or predict the risk of T. cruzi reactivation in PWH [ 36 ].…”
Section: Presentationsmentioning
confidence: 99%
“… 62 On the other hand, the protective role of IL17A AA, IL18 AA, and IL1B TC genotypes against development/progression of cardiomyopathy has been reported. 63 …”
mentioning
confidence: 99%